Correlation between physical attractiveness and athletic performance in amateur sports - Telebrico, Shawn Hendrix G. 1999-
ABSTRACT The general objective of this study is to determine if there wilj be a significant correlation between physical attractiveness and athletic performance in male and female amateur lawn tennis players in the Philippines. This study used a correlational research design to investigate the relationship between physical attractiveness and athletic performance. The determining factor for the athletic performance of the amateur tennis players will be the ranking leaderboard from the Unified Tennis Philippines Then an online questionnaire with images of tennis players and a five-point Likert scale was conducted to assess the attractiveness of these amateur tennis players which was answered by 60 college students studying in Metro Manila, Philippines. Using the spearman’s rank correlation coefficient to identify the correlation between the two variables, it was found that there is a significant correlation between physical attractiveness and athletic performance for males (rs = -0.5312, p = 0.015, two-tailed) but not for females (rs = -0.00829, p = 0.972, two-tailed). This study is significant because it can highlight the attractiveness halo effect or attractiveness bias with the intent to eliminate, if not at least minimize, its impact on society, specifically in the sports industry in the Philippines. Moreover, with the given advantages of attractiveness for athletes, coaches would have an additional factor in assessing the athlete and the success of the club.